2012
DOI: 10.1074/jbc.r112.399444
|View full text |Cite
|
Sign up to set email alerts
|

The Choreography of HIV-1 Proteolytic Processing and Virion Assembly

Abstract: HIV-1 has been the target of intensive research at the molecular and biochemical levels for >25 years. Collectively, this work has led to a detailed understanding of viral replication and the development of 24 approved drugs that have five different targets on various viral proteins and one cellular target (CCR5). Although most drugs target viral enzymatic activities, our detailed knowledge of so much of the viral life cycle is leading us into other types of inhibitors that can block or disrupt proteinprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
128
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 98 publications
(78 reference statements)
1
128
0
1
Order By: Relevance
“…For 10 patients (5,7,11,13,(15)(16)(17)(18)(19)(20) there were no changes in protease at failure, although nine had baseline protease polymorphisms.…”
Section: Predicted Hla and Kir Immune Escape Mutations In Gagmentioning
confidence: 99%
See 1 more Smart Citation
“…For 10 patients (5,7,11,13,(15)(16)(17)(18)(19)(20) there were no changes in protease at failure, although nine had baseline protease polymorphisms.…”
Section: Predicted Hla and Kir Immune Escape Mutations In Gagmentioning
confidence: 99%
“…[4][5][6] PI drug resistance is mediated by an accumulation of major mutations in the protease gene resulting in reduced binding of the inhibitor to the protease (PR) enzyme and high level resistance. 7 In addition, minor PR mutations, which have little or no effect on PI susceptibility, contribute to reduced susceptibility in combination with major mutations. 8 Studies have shown that mutations in Gag cleavage sites (CS) also contribute to PI resistance development.…”
mentioning
confidence: 99%
“…Ultrastructural analysis of HIV-1 tethered to human cells has been limited chiefly to examinations of chemically fixed and heavy-metal-stained samples by either thin-section transmission electron microscopy (TEM) (1,9,23,32,(35)(36)(37)(38) or scanning electron microscopy (SEM) (2,23,39). In previous studies, clusters of HIV-1 virions retained on the surface of infected or transfected cells expressing tetherin were consistently observed.…”
mentioning
confidence: 99%
“…In addition, NC and genomic RNA (gRNA) undergo transition from an immature to a condensed mature conformation upon processing of Gag (70,71). Interestingly, the cleavage of SP1/NC is the first step of particle maturation, while the C terminus of NC is released (NC/SP2 cleavage) concurrently with the final step of Gag maturation, i.e., the C-terminal cleavage of CA (68). Thus, strictly controlled timing of the maturation process holds CA and NC/RNA in their immature conformations, and sequential release of SP domains controls transformation of all these components into the mature core.…”
Section: Discussionmentioning
confidence: 99%
“…Structural transition of CA from the immature particle conformation into that of the mature core requires proteolytic liberation of both termini. While the release of the HIV CA N terminus is the second proteolytic step, the release of the CA C terminus is the final step of Gag maturation (68). The formation of an N-terminal ␤-hairpin, a critical structural element of the mature CA-NTD conformation, not only takes place upon liberation of the N-terminal proline of CA, but also requires proteolytic action at the opposite site of CA, releasing CTD-CA from downstream SP-1 (69).…”
Section: Discussionmentioning
confidence: 99%